GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMKN 1 TEGALLALANG - Kartika Dewi, Ni Luh Putu; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT Leadership style system is an important aspect in the world of education, because the leader is required the resources so that they are able to competate in the global world. For improving teacher performance, effective, dynamic, flexible and update leadership is need. Method of this research used qualitative approach. Where the technical data collection uses three ways, namely observation, interviews and documentation. The results of this research is show that the leadership of vocational high school nomor 1 Tegallalang is a democratic leadership system Keywords:Leadership Style, Teacher Performance